Who Were the Women? An In-Depth Analysis of Some Early Women Adult Educators - Susan Imel; Gretchen T. Bersch (Adult Education Research Conference, 2009)
This analysis of early women adult educators focuses on four women –Lucy Wilcox dams, Jesse Charters, Mary L. Ely, and Dorothy Canfield Fisher—who contributed to the early development of the field.